2018
DOI: 10.1007/s10597-018-0240-1
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Violence Victims in Shelters: What Do We Know About Their Mental Health?

Abstract: In this study, the relationship between mental disorders, childhood trauma and sociodemographic characteristics was evaulated in women staying in shelters due to domestic violence. The study comprised 59 volunteers, staying in women's shelters in Istanbul due to domestic violence. The structured clinical interview for DSM-IV TR axis 1 disorders (SCID-I), Domestic Violence Data Form, Hamilton Rating Scale for Depression, Beck Anxiety Inventory and Childhood Trauma Questionnaire were applied by a psychiatric exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…Mental health problems are also highly prevalent among the victims of IPV (Karakurt et al, 2014;Oram et al, 2017). Victims frequently report experiencing a broad range of Post-Traumatic Stress Disorder symptoms (Schnurr and Green, 2004;Afifi et al, 2009;World Health Organization, 2013;Akyazi et al, 2018). Past research also reports the association between IPV and an increased likelihood of clinical depression and suicide attempts (Mapayi et al, 2012;Akyazi et al, 2018).…”
Section: Effectiveness Of Treatments For Adverse Effects Of Intimate ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Mental health problems are also highly prevalent among the victims of IPV (Karakurt et al, 2014;Oram et al, 2017). Victims frequently report experiencing a broad range of Post-Traumatic Stress Disorder symptoms (Schnurr and Green, 2004;Afifi et al, 2009;World Health Organization, 2013;Akyazi et al, 2018). Past research also reports the association between IPV and an increased likelihood of clinical depression and suicide attempts (Mapayi et al, 2012;Akyazi et al, 2018).…”
Section: Effectiveness Of Treatments For Adverse Effects Of Intimate ...mentioning
confidence: 99%
“…Victims frequently report experiencing a broad range of Post-Traumatic Stress Disorder symptoms (Schnurr and Green, 2004;Afifi et al, 2009;World Health Organization, 2013;Akyazi et al, 2018). Past research also reports the association between IPV and an increased likelihood of clinical depression and suicide attempts (Mapayi et al, 2012;Akyazi et al, 2018). Comorbidities of multiple mental health issues are also common such as depression, anxiety, and PTSD among IPV victims (Schnurr and Green, 2004;World Health Organization, 2013).…”
Section: Effectiveness Of Treatments For Adverse Effects Of Intimate ...mentioning
confidence: 99%
“…There is also a substantial and probably underestimated economic burden of IPV for health services, through outpatient visits and use of hospital care . Finally, women who experience IPV are at greater risk of homelessness, and extremely high levels of psychiatric morbidity are evident in women living in domestic violence shelters …”
Section: The Mental Health Effects Of Experiencing Violencementioning
confidence: 99%
“…23 Finally, women who experience IPV are at greater risk of homelessness, and extremely high levels of psychiatric morbidity are evident in women living in domestic violence shelters. 27 Although injuries are intuitively the most likely consequence of assault, around 50% of general population participants who reported assault in the 2002-2003 British Crime Survey (BCS) reported no injury. More than one-tenth of assaults resulted in medical attention, and a third of instances involved wounding.…”
Section: The Mental Health Effects Of Experiencing Violencementioning
confidence: 99%
“…For example, a study of 59 survivors living in domestic violence shelters in Istanbul found that 76.3% were diagnosed with at least one psychiatric disorder, and posttraumatic stress disorder was the most common diagnosis (50.8%). In addition, over half of the women in their sample had attempted suicide at least once, and 66% of these were found to have attempted suicide after the violence started [ 46 ]. Much more research that systematically compares levels of distress in GBV survivors is needed.…”
Section: Discussionmentioning
confidence: 99%